Chemical compositions of solid particles present in the Greenland NEEM ice core over the last 110, 000 years. Issue 18 (28th September 2015) - Oyabu, Ikumi; Iizuka, Yoshinori; Fischer, Hubertus; Schüpbach, Simon; Gfeller, Gideon; Svensson, Anders; Fukui, Manabu; Steffensen, Jørgen Peder; Hansson, Margareta
Abstract: This study reports the chemical composition of particles present along Greenland's North Greenland Eemian Ice Drilling (NEEM) ice core, back to 110, 000 years before present. Insoluble and soluble particles larger than 0.45 µm were extracted from the ice core by ice sublimation, and their chemical composition was analyzed using scanning electron microscope and energy dispersive X‐ray spectroscopy and micro‐Raman spectroscopy. We show that the dominant insoluble components are silicates, whereas NaCl, Na2 SO4, CaSO4, and CaCO3 represent major soluble salts. For the first time, particles of CaMg(CO3 )2 and Ca(NO3 )2 4H2 O are identified in a Greenland ice core. The chemical speciation of salts varies with past climatic conditions. Whereas the fraction of Na salts (NaCl + Na2 SO4 ) exceeds that of Ca salts (CaSO4  + CaCO3 ) during the Holocene (0.6–11.7 kyr B.P.), the two fractions are similar during the Bølling‐Allerød period (12.9–14.6 kyr B.P.). During cold climate such as over the Younger Dryas (12.0–12.6 kyr B.P.) and the Last Glacial Maximum (15.0–26.9 kyr B.P.), the fraction of Ca salts exceeds that of Na salts, showing that the most abundant ion generally controls the salt budget in each period. High‐resolution analyses reveal changing particle compositions: those in Holocene ice show seasonal changes, and those in LGM ice show a difference between cloudy bands and clear layers, which again can be largely explained by the availability of ionic components in the atmospheric aerosol body of air masses reaching Greenland. Key Points: Sublimation analysis was done on the Greenland NEEM ice core The major soluble salt particles are NaCl, Na2 SO4, CaSO4, and CaCO3 The fraction of primary aerosol is higher than that in inland Antarctica